Characterizing the Impact of COVID-19 on Men Who Have Sex with Men Across the United States in April, 2020 - Sanchez, Travis H.; Zlotorzynska, Maria; Rai, Mona; Baral, Stefan D. (AIDS and behavior, 2020)
The COVID-19 pandemic is reinforcing health inequities among vulnerable populations, including men who have sex with men (MSM). We conducted a rapid online survey (April 2 to April 13, 2020) of COVID-19 related impacts on the sexual health of 1051 US MSM. Many participants had adverse impacts to general wellbeing, social interactions, money, food, drug use and alcohol consumption. Half had fewer sex partners and most had no change in condom access or use. Some reported challenges in accessing HIV testing, prevention and treatment services. Compared to older MSM, those 15–24 years were more likely to report economic and service impacts. While additional studies of COVID-19 epidemiology among MSM are needed, there is already evidence of emerging interruptions to HIV-related services. Scalable remote solutions such as telehealth and mailed testing and prevention supplies may be urgently needed to avert increased HIV incidence among MSM during the COVID-19 pandemic era.